2022
DOI: 10.1186/s12916-022-02364-7
|View full text |Cite
|
Sign up to set email alerts
|

Survival among people hospitalized with COVID-19 in Switzerland: a nationwide population-based analysis

Abstract: Background Increasing age, male sex, and pre-existing comorbidities are associated with lower survival from SARS-CoV-2 infection. The interplay between different comorbidities, age, and sex is not fully understood, and it remains unclear if survival decreases linearly with higher ICU occupancy or if there is a threshold beyond which survival falls. Method This national population-based study included 22,648 people who tested positive for SARS-CoV-2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Individuals aged 60–79 years presented a relative risk of lower survival of 1.62 ( p < 0.0001) compared to individuals aged 0–59 years, while a risk of 2.56 ( p < 0.001) was observed in the age group 80 years or older. This finding corroborates other studies [ 3 , 11 , 12 , 18 ]. Elderly patients with COVID-19 are subject to progress to a severe disease, as they are more susceptible to a multisystem organ dysfunction and even organ failure.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Individuals aged 60–79 years presented a relative risk of lower survival of 1.62 ( p < 0.0001) compared to individuals aged 0–59 years, while a risk of 2.56 ( p < 0.001) was observed in the age group 80 years or older. This finding corroborates other studies [ 3 , 11 , 12 , 18 ]. Elderly patients with COVID-19 are subject to progress to a severe disease, as they are more susceptible to a multisystem organ dysfunction and even organ failure.…”
Section: Discussionsupporting
confidence: 94%
“…In terms of mortality, the elderly population was the most affected. In several countries, it was found that persons aged 60 years or older are more vulnerable to the disease [ 3 , 12 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic has affected mortality globally through direct and indirect effects. Infection with SARS-CoV-2 directly causes death in a small proportion of infected people, with variations in the infection-fatality ratio (IFR) depending on age (1), socio-economic position (2), vaccination status (3), intensive care unit capacity (4) and several other characteristics of individuals or communities. Combined with the high transmissibility of SARS-CoV-2, this resulted in more than 6 million laboratory-confirmed deaths globally as of July 12, 2022 (5).…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has affected mortality globally through direct and indirect effects. Infection with SARS-CoV-2 directly causes death in a small proportion of infected people, with variations in the infectionfatality ratio (IFR) depending on age 1 , socio-economic position 2 , vaccination status 3 , intensive care unit capacity 4 and several other characteristics of individuals or communities. Deaths directly attributable to SARS-CoV-2 infection may be both laboratory-confirmed deaths and deaths attributable to SARS-CoV-2 without testing (e.g., deaths following a heart attack or stroke 5,6 ).…”
mentioning
confidence: 99%